A study on the variation of forces and temperature in a friction stir welding process: A finite element approach. (August 2016) - Jain, Rahul; Pal, Surjya K.; Singh, Shiv B.
Abstract: A three dimensional coupled thermo-mechanical finite element model (FEM) is proposed to simulate a friction stir welding (FSW) process based on Lagrangian incremental technique. Since FSW is a large deformation process, workpiece is considered as a rigid visco-plastic material. The model has been developed for predicting forces, spindle torque, temperature and plastic strain for a butt welding between two AA2024-T4 metals having thickness of 5.9 mm each. The developed model has been validated with experimental results (forces, spindle torque) obtained from literature. Maximum force is obtained during the plunging phase of the tool and this makes tool susceptible to failure. Forces and spindle torque reduce with the increase in rotational speed due to increase in heat generation rate which is also reflected in temperature distribution. Effect of welding speed and frictional boundary condition are studied. Conical pin shape produces higher material velocity as compared to cylindrical with reduced plunge force.